Changes in Lipoproteins Associated with Treatment with Methotrexate or Combination Therapy in Early Rheumatoid Arthritis: Results from the TEAR Trial - Navarro-Millán, Iris (2013)
OBJECTIVE: To study changes in lipid profiles at 24 weeks among early rheumatoid arthritis (RA) patients participating in the Treatment of Early Rheumatoid Arthritis (TEAR) Trial randomized to initiate methotrexate plus etanercept (MTX+ETA), triple therapy (TT) [MTX plus sulfasalazine plus hydroxychloroquine] or aggressively-titrated MTX monotherapy. METHODS: The TEAR biorepository study had 459 participating patients. Total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were measured in serum plasma at 0 and 24 weeks. RESULTS: At 24 weeks, there were statistically significant mean increases in cholesterol levels in the MTX + ETA, TT, and MTX monotherapy arms, the observed increases were 31.4, 28.7 and 30 mg/dL in LDL-C; 19.3, 22.3 and 20.6 mg/dL in HDL-C and 56.8, 53 and 57.3 mg/dL values in TC (p < 0.001 all compared to baseline). There was a statistically significant decrease in TC/HDL-C ratio at 24 weeks in all 3 treatment groups from baseline. There was no difference in any lipid changes between the 3 treatment arms. After multivariable adjustment, change in C-reactive protein was associated with change in LDL-C (p=0.03), HDL-C (p=0.09), and TC (p=0.01), but disease activity score in 28-joints was not. Baseline glucocorticoid use was associated with changes in HDL-C (p=0.03) and TC (p=0.02). CONCLUSION: Levels of TC, LDL-C, and HDL-C increased equivalently shortly after initiation of MTX + ETA, TT and MTX monotherapy among early RA patients with active disease participating in a clinical trial. The clinical relevance of short term changes in traditional lipids on cardiovascular outcomes remains to be determined.